The implementation of decentralised biogas plants in Assam, NE India: the impact and effectiveness of the National Biogas and Manure Management Programme - Raha, Debadayita; Mahanta, Pinakeswar; Clarke, Michèle L. (Elsevier, 2014)
The Indian Government’s National Biogas and Manure Management Programme (NBMMP) aims to deliver renewable energy services to households across the country by incentivising the deployment of family-sized (<6m3) anaerobic (biogas) digesters. We investigated how NBMMP policy is implemented at three levels, from government and state nodal agency, via private contractors to households. We analysed the scheme across two districts in Assam, north-east India, interviewing stakeholders in rural households, state and non-state institutions. We found a top-down, supply-side approach which enables central government to set targets and require individual states to deploy the scheme. Participation in the NBMMP was found to deliver improved energy service outcomes to a majority of households that can afford to participate, although the level of knowledge and understanding of the technology amongst users was limited. Improved training of householders, and particularly women, is needed in relation to the maintenance of digesters, feedstock suitability and the environmental and potential livelihood benefits of digestate. A policy revision which highlights the contextual and demand-side issues around adopting the technology, may deliver monetary benefits from market competition and enable development of community-focused microfinance schemes to improve the affordability of biogas systems.